Effect of testosterone treatment during puberty in boys with Klinefelter syndrome (The TIPY Study): protocol for a nationwide randomised, double-blinded, placebo-controlled study - Gary Butler; Anders Juul; Judith L Ross; Jørgen Holm Petersen; Kurt Kristensen; Ann-Margrethe Rønholt Christensen; Ida Dyhr Caspersen; Andrés Felipe Østergaard Fritzbøger; Niels Birkebæk; Anders Jørgen Schou; Shanlee Davis; Sophie van Rijn; et al. (BMJ Open)
Introduction Klinefelter syndrome (KS) is a genetic condition characterised by the presence of an extra X chromosome in males (47,XXY). KS is associated with various phenotypic characteristics in adult life, including infertility, hypogonadism and increased risk of type II diabetes, cardiovascular disease and osteoporosis. Additionally, individuals with KS often experience mental health challenges and functional impairments that significantly impact their quality of life. Currently, testosterone replacement therapy (TRT) in adolescence is considered the first-line treatment by some physicians for patients with KS and biochemical signs of hypogonadism. However, comprehensive evidence on its effectiveness in preventing typical phenotypic traits associated with KS remains limited, and, currently, no evidence-based recommendations for TRT in this population exist. We therefore aim to evaluate the effects of two years of TRT during puberty in boys with KS. The primary endpoint is to monitor changes in body fat percentage. Secondary endpoints include changes in pubertal development and virilisation, growth and body proportions, bone mineralisation, muscle strength, lipid and glucose metabolism, systemic inflammation, methylation, fertility and effects on the cognitive and psychopathological features of KS.Methods and analysis The TIPY study is a multicentre, national, randomised, double-blind, placebo-controlled intervention study. Participants will be recruited from four tertiary paediatric endocrine units in Denmark that manage boys with KS. Participants will be randomised to treatment with transdermal placebo or transdermal testosterone (Androgel; Besins Healthcare, Paris, France) with dose titration every 3 months based on individual measurements of serum concentrations of testosterone. Dose titration will be conducted by a single physician to ensure free testosterone remains between +1 and +3 SD for age.Thorough clinical and biochemical evaluation will be performed at baseline, after 12 months and 24 months. Additional visits for minor evaluations will occur every 3 months. Neuropsychological assessment will be conducted at baseline and after 24 months of treatment.Ethics and dissemination The study will be conducted in accordance with the Helsinki Declaration. The study has been approved by the Danish National Medical Research Ethics Committee and the Danish Medicines Agency (Clinical trials information system number 2023-505854-16-00). Results will be submitted for publication in peer-reviewed journals.Trial registration number NCT06294990.